2011
DOI: 10.1002/hep.24359
|View full text |Cite
|
Sign up to set email alerts
|

Serum and liver iron differently regulate the bone morphogenetic protein 6 (BMP6)-SMAD signaling pathway in mice

Abstract: The bone morphogenetic protein 6 (BMP6)-SMAD signaling pathway is a central regulator of hepcidin expression and systemic iron balance. However, the molecular mechanisms by which iron is sensed to regulate BMP6-SMAD signaling and hepcidin expression are unknown. Here, we examined the effects of circulating and tissue iron on Bmp6-Smad pathway activation and hepcidin expression in vivo after acute and chronic enteral iron administration in mice. We demonstrated that both transferrin saturation and liver iron co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
189
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(216 citation statements)
references
References 38 publications
20
189
1
6
Order By: Relevance
“…The expression of Smad7 has been linked to dietary iron 19, 20, 30. We thus have been suggested that feeding Smad7 Alb/Alb mice with an iron‐rich diet might induce a more robust phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Smad7 has been linked to dietary iron 19, 20, 30. We thus have been suggested that feeding Smad7 Alb/Alb mice with an iron‐rich diet might induce a more robust phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…We thus have been suggested that feeding Smad7 Alb/Alb mice with an iron‐rich diet might induce a more robust phenotype. According to the report, the hepcidin level reached to its peak at the 3rd day of iron‐rich diet treatment 30. We therefore choose a 3‐day iron‐rich diet treatment for the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, most high fat diet models induce metabolic changes but not fibrosis [66,67] . Furthermore, introduction of iron in the diet can create secondary effects by up-regulating liver hepcidin synthesis and thereby inhibiting the expression of iron exporter, ferroportin [68][69][70] . This will then lead to sequestration of iron in Kupffer cells and trigger inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular iron stores interact with hepcidin via the BMP6 pathway activating SMAD and increasing hepcidin levels. Circulating transferrin-bound iron exerts its effects via the haemochromatosis protein (HFE)/transferrin receptor 2 (TFR2) pathway (14,15). Mutations of these receptors are associated with hereditary haemochromatosis resulting in iron overload via dysregulated hepcidin expression (16,17).…”
Section: Iron Statusmentioning
confidence: 99%